2017
DOI: 10.1037/ocp0000027
|View full text |Cite
|
Sign up to set email alerts
|

Integrated and isolated impact of high-performance work practices on employee health and well-being: A comparative study.

Abstract: We investigate the positive relationships between High Performance Work Practices (HPWP) and employee health and well-being, and examine the conflicting assumption that high work intensification arising from HPWP might offset these positive relationships. We present new insights on whether the combined use (or integrated effects) of HPWP has greater explanatory power on employee health, well-being, and work intensification compared to their indicate that the combined use of HPWP may be sensitive to particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 42 publications
3
101
0
1
Order By: Relevance
“…through workplace productivity). Sceptics of the mutual gains perspective have raised concerns that the benefits of HR practices are often skewed in favour of the organisation at the expense of employee well-being (Ogbonnaya, Daniels, Connolly, & van Veldhoven, 2017). They argue that HR practices are utilised primarily to drive organisational performance and may thus be experienced by employees as a form of work intensification.…”
Section: Discussionmentioning
confidence: 99%
“…through workplace productivity). Sceptics of the mutual gains perspective have raised concerns that the benefits of HR practices are often skewed in favour of the organisation at the expense of employee well-being (Ogbonnaya, Daniels, Connolly, & van Veldhoven, 2017). They argue that HR practices are utilised primarily to drive organisational performance and may thus be experienced by employees as a form of work intensification.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported significant links between HRM systems and employee commitment (e.g., Gong et al, ; Gould‐Williams, ; Ogbonnaya et al, ; Paré & Tremblay, ). Paré and Tremblay's () study of 394 Canadian workers, for example, showed HRM practices are positively related to both the affective and continuance dimensions of commitment.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…By contrast, others argue that any performance benefits of HRM systems are offset by increased job demands, stress, and work intensification (Kroon, Van de Voorde, & Van Veldhoven, ; Ramsay, Scholarios, & Harley, ). HRM systems optimise employees' skills and performance, but with little or no benefit to their well‐being (Ogbonnaya, Daniels, Connolly, & Van Veldhoven, ). These competing views remain at the heart of HRM research and highlight the possibility of trade‐offs between the performance and well‐being benefits of HRM systems.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is evidence that high performance work systems are associated with better organisational performance (Combs et al 2006), links between high performance work systems and worker well-being are less clear (Van De Voorde, Paauwe, and Van Veldhoven 2012). However, a recent study indicates extensive use of high performance work systems, including high quality job design, is related to enhanced worker well-being, but that the moderate use of the underpinning employment practices may be related to low levels of well-being (Ogbonnaya et al 2017). Moreover, there is evidence that high performance work systems can be focused on specific organisational outcomes (Martinaityte, Sacramento, and Aryee in press), and it may be the case that high performance work systems have no beneficial or even adverse impacts on well-being if the system does not have worker well-being as one of its foci (Van De Voorde, Paauwe, and Van Veldhoven 2012).…”
Section: Job Design and Well-beingmentioning
confidence: 99%
“…In summary, both the socio-technical systems theory and the high performance work systems literatures indicate that job redesign needs to be integrated with other employment practices to enhance well-being and performance (Combs et al 2006;Davis et al 2013;Ogbonnaya et al 2017). This would suggest that other employment practices may augment job redesign, so that job redesign and some other employment practice(s) needs to be present in order to influence well-being and/or performance.…”
Section: Job Design and Well-beingmentioning
confidence: 99%